2006
DOI: 10.1590/s0102-86502006000900007
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo da cicatrização de gastrorrafias com e sem o uso do extrato de Jatropha gossypiifolia L. (pião roxo) em ratos

Abstract: The raw extract of Jatropha gossypiifolia L. aids the healing on the 3rd day post-surgery, concerning the enhanced resistance of the gastrographies to pressure of rupture, and on the 7th day, presenting better coaptation of the edges and reducing acute inflammatory reaction by microscopic analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
3
0
4
Order By: Relevance
“…Stomach was used as experimental organ by having the same morphological characteristics of the human and the gastrorraphy held in the region of the body due to technical facilities. However, a study analyzing the pattern of healing in incisional wounds in the walls of the stomach and duodenum of rats with polypropylene thread, the authors found that in intact tissue, the fundus is more extensible than the portion of the body, antrum and duodenum, requiring more energy to rupture 3,28,29,31,33 . In this study the dose of hydroalcoholic extract of aroeira chosen was 100 mg / kg / dose orally (gavage) by calculating the DL-50.…”
Section: Discussionmentioning
confidence: 99%
“…Stomach was used as experimental organ by having the same morphological characteristics of the human and the gastrorraphy held in the region of the body due to technical facilities. However, a study analyzing the pattern of healing in incisional wounds in the walls of the stomach and duodenum of rats with polypropylene thread, the authors found that in intact tissue, the fundus is more extensible than the portion of the body, antrum and duodenum, requiring more energy to rupture 3,28,29,31,33 . In this study the dose of hydroalcoholic extract of aroeira chosen was 100 mg / kg / dose orally (gavage) by calculating the DL-50.…”
Section: Discussionmentioning
confidence: 99%
“…A plausible hypothesis, not raised by the authors, could be the fact that the extract was administered in a single dose, which may not have been sufficient to maintain the effect throughout the time of the experiment. Additionally, Vale et al showed that the ethanolic extract from aerial parts of J. gossypiifolia , at single intraperitoneal dose of 200 mg/kg, favored the healing process of gastrorrhaphies and reduced the acute inflammatory reaction in vivo [ 123 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Estudos com fitoterápicos como o maracujá, aroeira, babaçu, pião roxo mostraram efeitos na cicatrização (BALDEZ et al 2006;BEZERRA et al 2006, GOMES et al 2006, VALE et al 2006. Essa alteração funcional pode ocasionar dores e alterações posturais mesmo em regiões distantes da lesão.…”
Section: Fatores Que Podem Influenciar Na Cicatrizaçãounclassified